Mesenchymal stem cells maintain their defining stem cell characteristics after treatment with cisplatin - Nicolay, Nils; Lopez Perez, Ramon; Rühle, Alexander; Trinh, Thuy; Sisombath, Sonevisay; Weber, Klaus-Josef; Ho, Anthony Dick; Debus, Jürgen; Saffrich, Rainer; Huber, Peter E. (Scientific reports, 2016)
Mesenchymal stem cells (MSCs) aid the regeneration of tissues damaged by treatment with cisplatin. However, the effects of this cytotoxic drug on the stem cells have been largely unknown. Here we demonstrate that human bone marrow-derived MSCs are relatively resistant to cisplatin treatment and show resistance levels comparable to these of differentiated fibroblasts. Cisplatin did not affect cellular morphology, adhesion or induction of apoptosis in MSCs. The potential for differentiation was preserved after exposure to cisplatin and established MSC surface markers were observed to be stably expressed irrespective of cisplatin treatment. Cytoskeletal rearrangements and high expression levels of individual heat shock proteins were detected in MSCs and may be partly responsible for the observed cisplatin resistance. The cisplatin-resistant phenotype of human MSCs supports the concept of further investigating these stem cells as a potential treatment option for cisplatin-induced tissue damage.
Gesehen am 27.10.2020